Effect of Light Emitting Diode (LED) Red Blue on the Production of Pakcoy (Brassica rapa L.) - Setiawan, Muhammad Azizi Rido; Wijaya, I Made Anom Sutrisna; Gunadnya, Ida Bagus Putu (Jurnal BETA (Biosistem dan Teknik Pertanian); Vol 11 No 1 (2023): April, 2022)
Abstract The horticulture sub-sector is one of the fundamental sectors for body nutrition. Pakcoy (Brassica Rapa L.) has good nutritional content, high economic value, and is widely found in Indonesia. Sunlight plays an important role in the photosynthesis process of plants so that the right spectrum and intensity of light will have an impact on the characteristics and yields of plants.  Therefore, artificial light is used to help agricultural activities.  This study aims to determine the effect of light intensity on the production of Pakcoy plants.  The research method was an experimental method that used Red (640-650 nm) and Blue LED lights (465-470 nm) with the light intensity of 1000 lux, 1500 lux, 2000 lux, 2500 lux, and 3000 lux, and applied for 12 hours.  The analytical method used is a completely randomized design analysis.  The results showed that the production of Pakcoy is significantly affected by red-blue LED light intensity, and the results showed that pakcoy biomass which uses a light intensity of 3000 lux to get the best results from other treatments, with the average value of the crown and root sizes of 0.6222 units(gram) and 0.0424 units(gram), respectively.  The most effective and efficient light intensity for optimal production of Pakcoy was 3000 lux.  Where 3000 lux produces the highest production.  In conclusion, the greater the intensity of light given, the greater the production effect obtained by the Pakcoy.